2021
DOI: 10.1101/2021.07.23.453472
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The in vitro and in vivo potency of CT-P59 against Delta and its associated variants of SARS-CoV-2

Abstract: The Delta variant originally from India is rapidly spreading across the world and causes to resurge infections of SARS-CoV-2. We previously reported that CT-P59 presented its in vivo potency against Beta and Gamma variants, despite its reduced activity in cell experiments. Yet, it remains uncertain to exert the antiviral effect of CT-P59 on the Delta and its associated variants (L452R). To tackle this question, we carried out cell tests and animal study. CT-P59 showed reduced antiviral activity but enabled neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“… 74 The reduction of mAb neutralising activity by different circulating variants of interest and variants of concern of SARS-CoV-2 is shown in table 4 .
Spike mutations associated with resistance in vitro to clinically approved monoclonal antibodies Bamlanivimab 64 , 65 , 66 L452R (>100-fold reduction); E484D/K/Q (>100-fold reduction); G485P; F490S/L (100-fold reduction); Q493R/K (100-fold reduction); and S494P/R (100-fold reduction) Bebtelovimab 67 K444Q (>83-fold reduction) and V445A (>83-fold reduction) Casirivimab 64 E406W/D (50–93-fold reduction); K417E/N/R/T (25–100-fold reduction); V455T (>100-fold reduction); Y453F (>100-fold reduction); L455F (80-fold reduction); A475R (44-fold reduction); E484K/Q (20–55-fold reduction); F486x; F486K/L/R/S/V (>100-fold reduction); N487R (>100-fold reduction); and Q493E/K/R (25–100-fold reduction) Cilgavimab 66 , 68 , 69 , 70 E484K (3·2-fold reduction) Etesevimab 64 , 65 , 66 K417N/T (100-fold reduction); D420N (100-fold reduction); F456R/A/K (100-fold reduction); N460K/S/T/Y (50–100-fold reduction); I472D; A475R/V (20–100-fold reduction); E484K; N487R (100-fold reduction); G485P; and Q493R/K (100-fold reduction) Imdevimab 64 E406W (>100-fold reduction); N439K (25–100-fold reduction); N440K (28–96-fold reduction); K444L/M/N/Q/T (>100-fold reduction); V445A (>100-fold reduction); G446V (>100-fold reduction); N450D (9–32-fold reduction); Q498H (17-fold reduction); P499S (>100-fold reduction); and E484K (16-fold reduction) Regdanvimab 71 L452R (35-fold reduction); E484K (8·7-fold reduction); and N501Y (5·5-fold reduction) Sotrovimab 72 , 73 P337R/L/H/T (180–276-fold reduction) and E340K/A/G (27–300-fold reduction) Tixagevimab 66,68–70 E484K (4–11-fold reduction) and S982A (3·2-fold reduction) Data are sourced via the Stanford University Coronavirus Antiviral and Resistance Database (accessed online on March 4, 2021, at https://covdb.stanford.edu/search-drdb ).
…”
Section: Resistance To Mabsmentioning
confidence: 99%
“… 74 The reduction of mAb neutralising activity by different circulating variants of interest and variants of concern of SARS-CoV-2 is shown in table 4 .
Spike mutations associated with resistance in vitro to clinically approved monoclonal antibodies Bamlanivimab 64 , 65 , 66 L452R (>100-fold reduction); E484D/K/Q (>100-fold reduction); G485P; F490S/L (100-fold reduction); Q493R/K (100-fold reduction); and S494P/R (100-fold reduction) Bebtelovimab 67 K444Q (>83-fold reduction) and V445A (>83-fold reduction) Casirivimab 64 E406W/D (50–93-fold reduction); K417E/N/R/T (25–100-fold reduction); V455T (>100-fold reduction); Y453F (>100-fold reduction); L455F (80-fold reduction); A475R (44-fold reduction); E484K/Q (20–55-fold reduction); F486x; F486K/L/R/S/V (>100-fold reduction); N487R (>100-fold reduction); and Q493E/K/R (25–100-fold reduction) Cilgavimab 66 , 68 , 69 , 70 E484K (3·2-fold reduction) Etesevimab 64 , 65 , 66 K417N/T (100-fold reduction); D420N (100-fold reduction); F456R/A/K (100-fold reduction); N460K/S/T/Y (50–100-fold reduction); I472D; A475R/V (20–100-fold reduction); E484K; N487R (100-fold reduction); G485P; and Q493R/K (100-fold reduction) Imdevimab 64 E406W (>100-fold reduction); N439K (25–100-fold reduction); N440K (28–96-fold reduction); K444L/M/N/Q/T (>100-fold reduction); V445A (>100-fold reduction); G446V (>100-fold reduction); N450D (9–32-fold reduction); Q498H (17-fold reduction); P499S (>100-fold reduction); and E484K (16-fold reduction) Regdanvimab 71 L452R (35-fold reduction); E484K (8·7-fold reduction); and N501Y (5·5-fold reduction) Sotrovimab 72 , 73 P337R/L/H/T (180–276-fold reduction) and E340K/A/G (27–300-fold reduction) Tixagevimab 66,68–70 E484K (4–11-fold reduction) and S982A (3·2-fold reduction) Data are sourced via the Stanford University Coronavirus Antiviral and Resistance Database (accessed online on March 4, 2021, at https://covdb.stanford.edu/search-drdb ).
…”
Section: Resistance To Mabsmentioning
confidence: 99%
“…Regdanvimab is a class I neutralizing monoclonal antibody that blocks ACE2 receptors and binds to the RBD [ 26 27 ]. Although regdanvimab has been shown to reduce the death rate and ameliorate weight loss in ACE2-transgenic mice infected with the Delta variant, it showed reduced binding affinity and susceptibility to regdanvimab, and the neutralizing activity of regdanvimab against the Delta variant was lower than that against the original strain of SARS-VoV-2 in vitro [ 28 ]. In addition, regdanvimab has reduced neutralizing activity against the Omicron variant in vitro [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…EUA-approved sotrovimab targets the highly conserved epitope of the receptor binding domain (RBD) of the S spike protein and blocks the attachment of S protein to ACE2 (52). While regdanivimab displays strong neutralizing activity against the Delta variant with 100% survival rate in pre-clinical studies, phase III clinical data revealed reduction in the COVID-19-related hospitalization, death, and/or reduction in the recovery time of high-risk patients (53)(54)(55).…”
Section: Discussionmentioning
confidence: 99%